SERANGGA HAMA TERKINI YANG MENYERANG TANAMAN SENGON (Falcataria moluccana (Miq.) Berneby & J.W Grimes) DAN JABON (Neolamarckia cadamba (Roxb.) Bosser) - Illa Anggraeni; Neo Endra Lelana; Agus Ismanto (Universitas Nusa Bangsa, 2019)
The Latest Insect Pests which Attacks Sengon (Falcataria moluccana (Miq.) Berneby & J.W Grimes) and Jabon Trees (Neolamarckia cadamba (Roxb.) Bosser)The current study of pest insect infestation on sengon (Falcataria moluccana (Miq.) Berneby & J.W Grimes)) and jabon (Neolamarckia cadamba (Roxb.) Bosser) plants has been carried out. The aimed of the study was to identify the latest status of the pests that infested sengon and Jabon plants. The research method used were field survey and observation in the laboratory. The survey was carried out in plantations owned by the Unit II Perhutani Unit in East Java as well as the small scale forests in the Kediri (East Java), Ciamis and Garut (West Java) areas. While observations in the laboratory were conducted at the Pest Laboratory of the Center for Forest Research and Development, Bogor. The results showed that pests that infested sengon and Jabon plants were unknown name of sengon shoot borer, Echinothrips sp. (Tripidae; Thysanoptera), horn beetle Oryctes rhinoceros (Scarabaeidae; Coleoptera), wild silkworm Attacus atlas (Saturniidae; Lepidoptera), leaf-sucking pests Lawana sp./Samurus sp. (Flatidae; Homoptera).Keywords: pest insect, sengon plant, jabon plant, the latest.ABSTRAKPenelitian tentang serangga hama terkini yang menyerang tanaman sengon (Falcataria moluccana) dan jabon (Neolamarckia cadamba) di hutan tanaman, bertujuan untuk menginventarisir jenis-jenis hama yang menyerang tanaman sengon dan jabon saat kini. Metode penelitian yang digunakan adalah metode survei dan pengamatan di laboratorium. Survei dilakukan di hutan tanaman milik Perum Perhutani maupun hutan milik rakyat di daerah Kediri, Ciamis dan Garut. Pengamatan di laboratorium dilakukan di Laboratorium Hama Pusat Penelitian dan Pengembangan Hutan, Bogor. Hasil penelitian menunjukkan bahwa hama yang menyerang tanaman sengon dan jabon adalah hama penggerek pucuk sengon (Pyralidae; Lepidoptera),hama Echinothrips sp. (Tripidae; Thysanoptera), kumbang tanduk Oryctes rhinoceros (Scarabaeidae; Coleoptera), ulat sutera liarAttacus atlas(Saturniidae; Lepidoptera), hama pengisap daun Lawana sp./Sanurus sp. (Flatidae; Homoptera).Kata kunci: serangga hama, tanaman sengon, tanaman jabon